View of nature of science (VNOS) form B: An instrument for assessing pre-service teacherâs view of nature of science at Borneo University Tarakan - Listiani, Listiani; Kusuma, Arieaf Ertha (University of Muhammadiyah Malang, 2017)
VNOS form B is an instrument that has been developed and revised to assess the view of nature of science of preservice science teachers through nature of science aspects.Indeed, students and teachers have to have the view of nature of science to avoid misconceptions of science concepts. Unfortunately, research on the view of Nature of Science is less conducted in Indonesia. This is a qualitative research that was conducted in Borneo University Tarakan. Respondents are preservice biology teachers in the sixth semester. The first step of this research is translating and adapting the VNOS form B into Bahasa Indonesia to make sure that the instrument is culturally fit to Indonesian and the transadapted instrument then given to the respondents. The result shows that the VNOS form B can be applied to assess the view of nature of science of preservice biology teachers. However, the result also shows that most of preservice biology teachers have few understanding on aspects of nature of scince.